Musing - Jonathan Locke Hart (Mingling Voices, 2011)
Musing is a book of sonnets. Working within the framework of a classic poetic form, Jonathan Locke Hart embarks on an extended meditation on our rootedness in landscape and in the past. As sonnets, the poems are a mixture of tradition and innovation. Throughout, Hart deftly interweaves European culture with North American settings and experience. The collection opens with a foreword by noted literary scholar Gordon Teskey, who reflects on the themes that have marked the evolution of Hart's poetry. Of Musing, Teskey writes: "These deeply thoughtful poems bring layered historical consciousness into the sonnet. They also touch and stir the heart through all its levels."